Combination Therapy With Lysin CF-301 and Antibiotic Is Superior to Antibiotic Alone for Treating Methicillin-Resistant Staphylococcus aureus–Induced Murine Bacteremia - Schuch, Raymond (Oxford University Press, 2014)
Lysins are bacteriophage-derived enzymes that degrade bacterial peptidoglycans. Lysin CF-301 is being developed to treat Staphylococcus aureus because of its potent, specific, and rapid bacteriolytic effects. It also demonstrates activity on drug-resistant strains, has a low resistance profile, eradicates biofilms, and acts synergistically with antibiotics. CF-301 was bacteriolytic against 250 S. aureus strains tested including 120 methicillin-resistant S. aureus (MRSA) isolates. In time-kill studies with 62 strains, CF-301 reduced S. aureus by 3-log(10) within 30 minutes compared to 6–12 hours required by antibiotics. In bacteremia, CF-301 increased survival by reducing blood MRSA 100-fold within 1 hour. Combinations of CF-301 with vancomycin or daptomycin synergized in vitro and increased survival significantly in staphylococcal-induced bacteremia compared to treatment with antibiotics alone (P < .0001). Superiority of CF-301 combinations with antibiotics was confirmed in 26 independent bacteremia studies. Combinations including CF-301 and antibiotics represent an attractive alternative to antibiotic monotherapies currently used to treat S. aureus bacteremia.